Polymorphism in cytochrome P4502A6 reduces the risk to head and neck cancer and modifies the treatment outcome. (26th October 2021) - Yadav, Vinay Kumar; Katiyar, Tridiv; Ruwali, Munindra; Yadav, Sanjay; Singh, Sudhir; Hadi, Rahat; Bhatt, Madan Lal Brahma; Parmar, Devendra
Abstract: The present case–control study consisting of 1300 cases of head and neck squamous cell carcinoma (HNSCC) and the equal number of controls aimed to investigate the association of functionally important polymorphisms in cytochrome P4502A6 ( CYP2A6*1B, CYP2A6*4C, CYP2A6*9‐ rs28399433) with HNSCC and the treatment response in cases receiving a combination of chemotherapy/radiotherapy (CT/RT). A significant decrease in risk to HNSCC was observed in the cases with deletion ( CYP2A6*4B and CYP2A6*4C ) or reduced activity genotypes ( CYP2A6*9 ) of CYP2A6 . This risk to HNSCC was further reduced significantly in tobacco users among the cases when compared to nontobacco users among the cases. The risk was also reduced to a slightly greater extent in alcohol users among the cases when compared to nonalcohol users among the cases. In contrast with decreased risk to HNSCC, almost half of the cases with variant genotypes of CYP2A6 ( CYP2A6*1A/*4C+*1B/*4C+*4C/*4C and *9/*9 ) did not respond to the treatment. Likewise, the survival rate in cases receiving the treatment, after 55 months of follow‐up was significantly lower in cases with deletion (6.3%) or reduced activity (11.9%) allele than in the cases with common alleles (41%). The present study has shown that CYP2A6 polymorphism significantly reduces the risk to HNSCC. Our data further suggested that CYP2A6 polymorphism may worsen the treatment outcome in the cases receiving CT/RT.